Unbound: my story of liberation and the birth of the Me Too movement - Burke, Tarana (Headline Publishing Group, 2021)
From the founder and activist behind one of the largest movements of the twenty-first century, the me too movement, Tarana Burke debuts a powerful memoir about her own journey to saying those two simple yet infinitely powerful words and how she brought empathy back to an entire generation 'Searing. Powerful. Needed.' Oprah 'I will never stop thinking about this book.' Glennon Doyle Tarana didn't always have the courage to say me too. As a child, she reeled from her sexual assault, believing she was responsible. Unable to confess what she thought of as her own sins for fear of shattering her family, her soul split in two. One side was the bright, intellectually curious third generation Bronxite steeped in Black literature and power, and the other was the bad, shame ridden girl who thought of herself as a vile rule breaker, not of a victim. She tucked one away, hidden behind a wall of pain and anger, which seemed to work... until it didn't